2009
DOI: 10.2337/db09-0618
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Glucose-Lowering Therapy Reduces Cardiovascular Disease Events in Veterans Affairs Diabetes Trial Participants With Lower Calcified Coronary Atherosclerosis

Abstract: OBJECTIVEThis study investigated the hypothesis that baseline calcified coronary atherosclerosis may determine cardiovascular disease events in response to intensive glycemic control within the Veterans Affairs Diabetes Trial (VADT).RESEARCH DESIGN AND METHODSAt baseline, 301 type 2 diabetic participants in the VADT, a randomized trial comparing the effects of intensive versus standard glucose lowering on cardiovascular events, had baseline coronary atherosclerosis assessed by coronary artery calcium (CAC) mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
112
1
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(124 citation statements)
references
References 21 publications
6
112
1
5
Order By: Relevance
“…13 Although certainly not definitive, these findings from VADT and AC-CORD suggest that intensive glucose control may reduce CV events in patients with a shorter duration of DM and in those who do not have significant preexisting CAD. 7,14 After a median follow-up of 5 years, the ADVANCE (Action in Diabetes and Vascular Disease: Preterax and Diamicron Modified Release Controlled Evaluation) trial showed no difference between intensive control and standard control groups in macrovascular outcomes. [13][14][15] Mean HbA 1c values achieved in the ADVANCE study were 6.5% in the intensive control group and 7.3% in the standard control group.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…13 Although certainly not definitive, these findings from VADT and AC-CORD suggest that intensive glucose control may reduce CV events in patients with a shorter duration of DM and in those who do not have significant preexisting CAD. 7,14 After a median follow-up of 5 years, the ADVANCE (Action in Diabetes and Vascular Disease: Preterax and Diamicron Modified Release Controlled Evaluation) trial showed no difference between intensive control and standard control groups in macrovascular outcomes. [13][14][15] Mean HbA 1c values achieved in the ADVANCE study were 6.5% in the intensive control group and 7.3% in the standard control group.…”
mentioning
confidence: 99%
“…7,14 After a median follow-up of 5 years, the ADVANCE (Action in Diabetes and Vascular Disease: Preterax and Diamicron Modified Release Controlled Evaluation) trial showed no difference between intensive control and standard control groups in macrovascular outcomes. [13][14][15] Mean HbA 1c values achieved in the ADVANCE study were 6.5% in the intensive control group and 7.3% in the standard control group. 11 Similar to ACCORD and VADT, the rate of combined primary end point (composite of microvascular and macrovascular events) was significantly lower with intensive vs conservative glucose control among patients who did not have established CV disease at baseline.…”
mentioning
confidence: 99%
“…Overall the glycemic differences between the treatment arms were small and the primary outcome was neutral, however, patients with shorter diabetes duration (i.e., less than 5 years) had reduced risk [hazard ratio (HR) = 0.74 (95%CI: 0.54, 1.01)] for the composite primary CV endpoint as compared to those with longer disease duration [5-10 years HR = 0.81 (95%CI: 0.58, 1.13); > 10 years HR = 1.22 (95%CI: 0.98, 1.53); interaction with treatment P-value 0.014]. Another interesting observation in the context of degree of vasculopathy as a potential determinant for the effect of an intervention stems from the veterans affairs diabetes trial (VADT) [13] . The VADT tested whether intensive glucose control (targeted/achieved HbA1c < 6.0%/6.9%) vs conventional (targeted/achieved HbA1c < 9.0%/8.9%) could reduce CV risk in 1791 patients with long-standing T2D [13] .…”
Section: The Relevance Of Contextualizing Outcome Trial Results To T2mentioning
confidence: 99%
“…Another interesting observation in the context of degree of vasculopathy as a potential determinant for the effect of an intervention stems from the veterans affairs diabetes trial (VADT) [13] . The VADT tested whether intensive glucose control (targeted/achieved HbA1c < 6.0%/6.9%) vs conventional (targeted/achieved HbA1c < 9.0%/8.9%) could reduce CV risk in 1791 patients with long-standing T2D [13] . Although intensive glucoselowering therapy did not significantly reduce CV events in the study cohort as a whole, there was evidence that the response was modified by baseline CAC.…”
Section: The Relevance Of Contextualizing Outcome Trial Results To T2mentioning
confidence: 99%
“…[24][25][26][27] However, the effect of intensive therapy on macrovascular disease is still unclear; epidemiological evidence and data from recent trials suggest there are benefits, particularly if treatment is initiated early in the course of the disease and in patients with a shorter duration of DM (less burden of CHD). [28][29][30][31][32] Two recent meta-analyses of clinical studies that evaluated intensive vs standard therapy and the risk of cardiovascular outcomes concluded that intensive therapy significantly reduced the risk of cardiovascular events but not cardiovascular death or all-cause mortality. 33,34 Continued research on the pathophysiology and potential new treatments for patients with type 2 DM is warranted despite improved efforts to reach glycemic targets.…”
Section: Diabetes Care: There Is Room For Improvementmentioning
confidence: 99%